Rhabdomyolysis associated with newer-generation anti-seizure medications (ASMs): a real-world retrospective and pharmacovigilance study - Zhenzhen Deng; Shengfeng Wang; Cuifang Wu (Frontiers Media S.A., 2023)
Objective: Rhabdomyolysis is a potentially fatal adverse reaction mostly triggered by certain medications. Few real-world studies have shown a clear association between newer-generation anti-seizure medications (ASMs) and rhabdomyolysis. We sought to quantify the risk and evaluate the clinical features and management of rhabdomyolysis associated with newer-generation ASMs.Methods: Data were retrieved from the US FDA Adverse Event Reporting System database (FAERS) from 2018 to 2022 on newer-generation ASMs to identify rhabdomyolysis events, and disproportionality analyses were conducted by estimating the reporting odds ratios (RORs) and corresponding 95% confidence intervals (CIs). Furthermore, case reports from 2012 to 31 December 2022 on newer-generation ASMs-induced rhabdomyolysis were retrieved for retrospective analysis.Results: A total of 1,130 rhabdomyolysis reports from the FAERS database were considered. Levetiracetam had the greatest proportion and the highest positive signal values of rhabdomyolysis. The RORs (95% CIs) for newer-generation ASMs were, in descending order, levetiracetam 8.01 (7.26-8.84), lamotrigine 3.78 (3.25-4.40), oxcarbazepine 3.47 (2.53-4.75), pregabalin 2.75 (2.43-3.12), lacosamide 1.85 (1.29-2.65), topiramate 1.64 (1.25-2.15), and gabapentin 1.32 (1.13-1.55). Twenty-six case reports showed evidence of rhabdomyolysis, and levetiracetam (65.4%) was the most frequently reported agent. The median age was 32 years; typical initial symptoms included muscle weakness (34.8%), myalgia (34.8%), backache (17.4%), fatigue (13.0%) and leg pain (8.7%). The median time to onset of rhabdomyolysis was 2 days. All cases had elevated creatine phosphokinase (CPK), and some cases were accompanied by elevated creatinine (57.1%) and myoglobinuria (53.8%). Cessation of ASMs could lead to complete clinical remission. The median time for creatine phosphokinase (CPK) normalization was 8 days.Conclusion: This study identified 7 newer-generation ASMs with significant rhabdomyolysis reporting associations. Prescribers should be more aware of this risk and teach patients to recognize rhabdomyolysis signs/symptoms early.